Vascular Malformations: A Histopathologic and Conceptual Appraisal - A. Fernandez-Flores; D. Cassarino; I. Colmenero (Elsevier, 2023)
In the field of vascular anomalies, distinguishing between vascular malformations and tumors has become crucial for a correct therapeutic approach. However, the differential diagnosis between these two groups is not always well explained in classical texts, mainly because many vascular malformations are still known with old names that suggest a tumoral nature. Also, genetic and pathogenic knowledge of these entities has greatly increased in recent decades, so researchers and clinicians now have a better understanding of vascular malformations. In this paper, we present the main histopathological tips to recognize and identify a vascular malformation as such. We also contextualize such information in the clinical and pathogenic knowledge for a better understanding of these entities. Resumen: En el campo de las anomalías vasculares, distinguir entre malformaciones vasculares y tumores vasculares se ha vuelto esencial para un enfoque terapéutico correcto. Sin embargo, el diagnóstico diferencial entre estos dos grupos no está siempre correctamente explicado en los textos clásicos, principalmente porque a muchas malformaciones vasculares se las conoce todavía con nombres antiguos que sugieren tumores vasculares. Asimismo, el conocimiento genético y patogénico de estas entidades se ha incrementado notablemente en las décadas recientes, de tal manera que investigadores y clínicos tienen ahora una mejor comprensión de las malformaciones vasculares. En este artículo, presentamos las principales claves histopatológicas para reconocer las malformaciones vasculares e identificarlas como tal. También contextualizamos tal información en el conocimiento clínico y patogénico para mejor comprensión de estas entidades.